Effects of Urban Transformation on a Modern Housing Area: Talimhane, Istanbul Example - Ozmen, Elifnaz Durusoy; Polat, Ebru Omay (KARE PUBL, 2021)
Istanbul has always been a flourishing metropolis with regard to the qualified cultural accumulation resulting from the traces of its historical stratification and the combination of these traces. With the advent of the 20th century, the modern architectural products are also a part of this accumulation. However, despite being involved under the definition of cultural heritage, they are perceived as elements destroying the historical environment. This situation resulted in the loss of modern architectural heritage through the misinterpreted practices of urban transformation. The protection of Turkeys modern architectural heritage is also on the agenda as a problematic issue discussed at different scales because of the transformation-oriented decisions. This study focuses on Talimhane, a modernist project designed and implemented in the first half of the 20th century. Within the scope of the article, Talimhane, which was an urban open space used as the military training place of Taksim Artillery Barracks in the past, is introduced with regards to its formation in the 1930s as a holistic residential area and its development in the 1940s. Then, the social, physical and functional transformation of the area, which has been under evolution since the 1950s, is emphasized and this transformation is documented with the help of current situation analyses. The conclusion part, which critically evaluates the destructive impacts of urban transformation on the modern architectural heritage, aims to draw attention on the existing potentials in the preservation of modern architectural heritage not limited to Talimhane case.
Keywords: Istanbul; urban transformation; modern architectural heritage; Talimhane; Public Administration